Muslim Post-Graduate Students’ Self-Leadership Skills and Productivity during Remote Teaching and Learning - Preece, Abdul Shakour Duncan; Hamed, Popoola Kareem (Cendekia: Kependidikan dan Kemasyarakatan, 2023)
The study aims to investigate the impact of self-leadership on Muslim postgraduate students’ achievement or productivity during remote teaching and learning in Malaysian higher education institutions. The research instrument was a Likert questionnaire that measured the dimensions of self-leadership and productivity. The study employed principal component analysis (PCA) and path analysis using AMOS. The findings supported self-leadership as a multidimensional construct with five underlying dimensions comprising self-determined goals, self-reward, self-punishment, self–observation and self-cueing. Several latent variables further supported each dimension. In addition, the results showed that the dimensions of self-leadership and productivity are psychometrically sound regarding divergent and convergent validity. The average variance explained for each variable was (> .05), and the values for composite reliability of the constructs ranged from (.887 and .910). Furthermore, the study found that the dimensions of self-leadership, i.e. self-goal, self-reward, self-punishment, self–observation and self-cueing, positively predicted Muslim students’ productivity during remote teaching and learning, with a p-value of less than 0.00. The study recommends promoting self-leadership strategies to enhance students’ productivity and, in turn, their overall educational performance.